1998
DOI: 10.1159/000010021
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Nitric Oxide/Endothelin-1 Equilibrium in Cultured Human Placental Endotheliocytes in Preeclampsia

Abstract: Several observations suggest that endothelial cell dysfunction is a central pathophysiologic event of preeclampsia. Endothelin-1 (ET-1) is a vasoconstrictor peptide of the endotheliocyte and is increased in the sera of preeclamptic patients. The aim of this study was to investigate the possible regulatory mechanisms between ET-1 and nitric oxide (NO) production in cultured placental endotheliocytes. We report that endothelial cells of arterial placental blood vessels show a dysfunctional mechanism of negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The higher levels of endothelin‐1 in most of the feto‐placental tissues from women with pre‐eclampsia may be due either to increased endothelin production or to decreased endothelin destruction or clearance in these tissues. Endothelin‐1 secretion by cultured endothelial cells from placental arteries from women with pre‐eclampsia has been reported to be higher (32). Whether the raised levels of endothelin in these tissues are directly or indirectly involved in the pathogenesis of pre‐eclampsia or are a reflection of the consequence of an overall abnormality in the feto‐placental unit is not possible to ascertain from this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher levels of endothelin‐1 in most of the feto‐placental tissues from women with pre‐eclampsia may be due either to increased endothelin production or to decreased endothelin destruction or clearance in these tissues. Endothelin‐1 secretion by cultured endothelial cells from placental arteries from women with pre‐eclampsia has been reported to be higher (32). Whether the raised levels of endothelin in these tissues are directly or indirectly involved in the pathogenesis of pre‐eclampsia or are a reflection of the consequence of an overall abnormality in the feto‐placental unit is not possible to ascertain from this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that uteroplacental vascular bed may be one of the sources for increased ET‐1 production in women with pre‐eclampsia (22). Endothelin‐1 release has been shown to be increased (23) and decreased in (24) cultured endotheliocytes and trophoblasts respectively. Reports on the levels of endothelins and its receptor profiles in the placenta are also somewhat conflicting (25–27).…”
mentioning
confidence: 99%
“…These defective responses may thus result in oxidative stress and increased interaction of NOS with O 2 − , production of ONOO − , and impaired NO bioactivity 27 . Increased concentration of the vasoconstrictor endothelin‐1 has also been reported in arterial endothelial cells of preeclamptic women, perhaps indicating dysfunctional NO response levels 29 …”
mentioning
confidence: 99%